Antioxidant Activities of Malaysian Plukenetia volubilis - Ismail, Muhammad Naqieb; Ismail, Nurul Izzati (Multidisciplinary Applied Research and Innovation, 2022)
Plukenetia volubilis (P. volubilis) also known as sacha peanut, inca peanut or mountain peanut belongs to the Euphorbiaceae family and contains antioxidants. In this study, Malaysian P. volubilis was used to study of total phenolic content (TPC) and the total of flavonoid content (TFC) along with its antioxidant activity by using 2,2- azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) method. The collected Malaysian P. volubilis’s dried kernel were separate from its shell to extract its oil by using cold pressed method. The Folin-Ciocalteu method was used to evaluate TPC, and the production of flavonoid-aluminium complex was used to estimate TFC. The ABTS radical cation decolorization assay was used to evaluate the ABTS free radical-scavenging activity. The result shows that the highest inhibition of the P. volubilis was 20.31% at 125 ppm and the IC50 value of ABTS sample was 4405.96 ppm meanwhile the results obtained for the total flavonoid was 2.50 RE ppm and total phenolic content was 2.90 GAE ppm. It was concluded that the Malaysian P. volubilis is a potential source of antioxidants agent. The data is  significant for the development of neutraceutical products as alternative and treatment to diseases related to cellular damage due to free radicals.